Who came first, the egg or the chicken? What comes first, psychological contract breach or perceived job insecurity? - Junça-Silva, A.; López, S. (International Journal of Manpower, 2025)
Purpose This study uses a job-demand resource perspective to test a conceptual model in which psychological contract breach has a negative relation with job performance (adaptivity and proficiency) through perceived job insecurity. Further, it has also been proposed that higher levels of role conflict will strengthen the impact of psychological contract breaches on job performance through job insecurity. Design/methodology/approach Two-wave data were collected from 449 working adults from the retail sector with managerial occupations in Chile. The moderated mediation models were tested through SPSS macro (developed by Preacher and Hayes, 2004). Findings The findings supported the hypotheses; first, psychological contract breach negatively influences job performance through job insecurity; and second, role conflict moderates the indirect relationship in a way that lower levels of role conflict buffer the relationship between psychological contract breach and job performance through job insecurity (versus higher levels of role conflict). Originality/value This study has practical and theoretical implications. On the one hand, it establishes how and when psychological contract breaches might harm individual job performance. On the other hand, it can be a guide to managers and employees who can find evidence about how harmful a breach of employees’ psychological contract can be.